Afroinscrições em Petrópolis: história, memória e territorialidades - Silva, Renata Aquino da (2018)
Territories are fundamental to the understanding of the technical and scientific inscriptions of black populations in Brazilian society. In this work, the geographic space of the city of Petrópolis was studied taking as parameters its Afro-inscriptions, also the settlement and the development of the region made by Africans and Afro-descendants. The research is inserted in the field of Afrodescendence, using the concepts of Afro-Descendant Urban Space and the formation of Afro-Descendent Territorialities. As parameters, the study presents the proposals of Pan-Africanism and authors such as Raul Ruiz Asúa Altuna, Clóvis Moura, Guerreiro Ramos, Henrique Cunha Junior, and Milton Santos. The history of the city of Petrópolis presents two ideologies, the first being a city resulting from 1843s German immigration and the second is the fact that it is an imperial city. From both perspectives, the alleged lack of important black population in this story is implied and reaffirmed in other ways. I argue against such an ideology, reaffirming and investigating the existence of African settlers from the various sources that can lead to the meeting of Afro-inscriptions as a material and intangible cultural heritage in the history and culture of the region. I start from the idea that the constitution of a territory subordinate to the Parish of Nossa Senhora de Inhomirim in the colonial period was due to the navigation of the Piabanha river, which was an important geographical element in the dynamics of the region’s territory, and due to the influx of populations from the surroundings, not only because of the gold route, as the issue of the region’s economy is generally addressed. The base of the region’s settlement was through the navigation of the Piabanha river and through the farms that exploited the slave labor. From the territory occupied by Africans and people of African descent, the city was formed, which later installed some groups of German immigrants. In this population fusion, a strong presence of black and white populations from other than German origin was constituted. Finally, I discuss the consequences of Afro-inscriptions in Petrópolis on the education and culture dimensions. This thesis is an approach to the development and settlement of Petrópolis from the perspective of the black population, under the proposals of pan-Africanism, which aims to contribute to the fulfillment of the provisions of law 10639/03.